Perioperative Outcomes and Trends in the Use of Robotic Colectomy for Medicare Beneficiaries From 2010 Through 2016 - Sheetz, Kyle H. (JAMA Surg, 2019)
IMPORTANCE: The use of robotic surgery for common operations like colectomy is increasing rapidly in the United States, but evidence for its effectiveness is limited and may not reflect real-world practice. OBJECTIVE: To evaluate outcomes of and trends in the use of robotic, laparoscopic, and open colectomy across diverse practice settings. DESIGN, SETTING, AND PARTICIPANTS: This population-based study of Medicare beneficiaries undergoing elective colectomy was conducted between January 2010 and December 2016. We used an instrumental variable analysis to account for both measured and unmeasured differences in patient characteristics between robotic, open, and laparoscopic colectomy procedures. Data were analyzed from January 21, 2019, to March 1, 2019. EXPOSURES: Receipt of robotic colectomy. MAIN OUTCOMES AND MEASURES: Incidence of postoperative medical and surgical complications and length of stay. RESULTS: A total of 191 292 procedures (23 022 robotic procedures [12.0%], 87 639 open procedures [45.8%], and 80 631 laparoscopic colectomy procedures [42.0%]) were included. Robotic colectomy was associated with a lower adjusted rate of overall complications than open colectomy (17.6% [95% CI, 16.9%-18.2%] vs 18.6% [95% CI, 18.4%-18.7%]; relative risk [RR], 0.94 [95% CI, 0.91-0.98]). This difference was driven by lower rates of medical complications (15.5% [95% CI, 14.8%-16.2%] vs 16.9% [95% CI, 16.7%-17.1%]; RR, 0.92 [95% CI, 0.87-0.96]) because surgical complications were higher with the robotic approach (3.0% [95% CI, 2.8%-3.2%] vs 2.4% [95% CI, 2.3%-2.5%]; RR, 1.18 [95% CI, 1.04-1.35]). There were no differences in complications between robotic and laparoscopic colectomy (11.1% [95% CI, 10.5%-11.6%] vs 11.0% [95% CI, 10.8%-11.2%]; RR, 1.00 [95% CI, 0.95-1.05]). There was an overall shift toward greater proportional use of robotic colectomy from 0.7% (457 of 65 332 patients) in 2010 to 10.9% (8274 of 75 909 patients) in 2016. In hospitals with the highest adoption of robotic colectomy between 2010 and 2016, increasing use of robotic colectomy (0.8% [100 of 12 522 patients] to 32.8% [5416 of 16 511 patients]) was associated with a greater replacement of laparoscopic operations (43.8% [5485 of 12 522 patients] to 25.2% [4161 of 16 511 patients]) than open operations (55.4% [6937 of 12 522 patients] to 41.9% [6918 of 16 511 patients]). CONCLUSIONS AND RELEVANCE: While robotic colectomy was associated with minimal safety benefit over open colectomy and had comparable outcomes with laparoscopic colectomy, population-based trends suggest that it replaced a greater proportion of laparoscopic rather than open colectomy, especially in hospitals with the highest adoption of robotics.